Anticancer and Cytotoxic Activities of [Cu(C6H16N2O2)2][Ni(CN)4] and [Cu(C6H16N2O2)Pd(CN)4] Cyanidometallate Compounds on HT29, HeLa, C6 and Vero Cell Lines - Aydın, Ali; Aslan Korkmaz, Sengul; Demir, Veysel; Tekin, Saban (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: In cancer, apoptosis relevant proteins—such as CaM kinase, Bcl-2 or P53, topoisomerase I, cell migration feature and DNA/BSA—macromolecules represent significant targets for current chemotherapeutics. Objective: We recently reported two coordination compounds—[Cu(C6H16N2O2)2][Ni(CN)4] (1) and [Cu(C6H16 N2O2)Pd(CN)4] (2)—together with their IR spectra, magnetic properties, thermal analyses and crystal structures. Herein, we describe the ability of these complexes to induce apoptosis in relevant proteins and stimulate topoisomerase I activity, cell migration velocity and DNA/BSA binding properties. Method: The in vitro antiproliferative effects and cell toxicity of both compounds were investigated through pharmacological measurement techniques, and interactions between both compounds and CT-DNA/BSA were studied with UV-Vis spectroscopy and fluorescence spectroscopy. Results & Conclusion: Studies on cells revealed that 2 (i) demonstrated a high antiproliferative effect, which was higher toward HeLa and C6 cancer cells than toward healthy Vero cells; (ii) impaired the migration of HeLa cells; (iii) altered the P53-Bcl-2 ratio in favor of apoptosis; (iv) strongly bound to DNA/BSA macromolecules; and (v) inhibited human topoisomerase I and KpnI or BamHI restriction endonucleases. In conclusion, this preliminary information demonstrates that 2 may represent a promising antiproliferative agent and a potential candidate for a therapeutic approach against HeLa.
Keywords: palladium